The maternal factor : two paths to morality - Noddings, Nel (University of California Press, 2010)
In this provocative new book, renowned educator and philosopher Nel Noddings extends her influential work on the ethics of care toward a compelling objective-global peace and justice. She asks: If we celebrate the success of women becoming more like men in professional life, should we not simultaneously hope that men become more like women-in caring for others, rejecting violence, and valuing the work of caring both publicly and personally? Drawing on current work on evolution, and bringing concrete examples from women's lived experience to make a strong case for her position, Noddings answers this question by locating one source of morality in maternal instinct. She traces the development of the maternal instinct to natural caring and ethical caring, offering a preliminary sketch of what a care-driven concept of justice might look like. Finally, to advance the cause of caring, peace, and women's advancement, Noddings urges women to abandon institutional, patriarchal religion and to seek their own paths to spirituality.